Multiband Circular Polarizer Based on Fission Transmission of Linearly Polarized Wave for X-Band Applications - Farman Ali Mangi; Shaoqiu Xiao; Ghulam Ali Mallah; Deedar Ali Jamro; Imran Memon; Ghulam Fatima Kakepoto (Journal of Electrical and Computer Engineering)
A multiband circular polarizer based on fission transmission of linearly polarized wave for x-band application is proposed, which is constructed of 2 × 2 metallic strips array. The linear-to-circular polarization conversion is obtained by decomposing the linearly incident x-polarized wave into two orthogonal vector components of equal amplitude and 90° phase difference between them. The innovative approach of “fission transmission of linear-to-circular polarized wave” is firstly introduced to obtain giant circular dichroism based on decomposition of orthogonal vector components through the structure. It means that the incident linearly polarized wave is converted into two orthogonal components through lower printed metallic strips layer and two transmitted waves impinge on the upper printed strips layer to convert into four orthogonal vector components at the end of structure. This projection and transmission sequence of orthogonal components sustain the chain transmission of electromagnetic wave and can achieve giant circular dichroism. Theoretical analysis and microwave experiments are presented to validate the performance of the structure. The measured results are in good agreement with simulation results. In addition, the proposed circular polarizer exhibits the optimal performance with respect to the normal incidence. The right handed circularly polarized wave is emitted ranging from 10.08 GHz to 10.53 GHz and 10.78 GHz to 11.12 GHz, while the left handed circular polarized wave is excited at 10.54 GHz–10.70 GHz and 11.13 GHz–11.14 GHz, respectively.